1985
DOI: 10.1093/ageing/14.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Erythrocyte Sedimentation Rate and Serum C-Reactive Protein Concentration in Elderly Patients

Abstract: Fifty-five consecutive admissions to an acute geriatric unit were studied prospectively. Individuals were classified according to the obvious presence or absence of an active disease process on admission and their serum C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were measured then and five days later. There was no significant difference between the ESR values in the two groups either on admission or at day 5, nor was there any significant change between admission and day 5. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…12 The majority of previous studies that have investigated the agreement between CRP and ESR values have included selected samples of patients with specific inflammatory diseases. 10,[13][14][15][16][17][18][19][20] More general studies comparing ESR and CRP have included patients with various diseases in the hospital [21][22][23][24][25][26] and primary care settings. [27][28][29] In general, CRP and ESR have similar diagnostic accuracy assessing acute inflammation, 10 though CRP tends to be more reliable for disease monitoring because CRP levels change faster than the ESR 12,26,27 and are less affected by patient age.…”
Section: Introductionmentioning
confidence: 99%
“…12 The majority of previous studies that have investigated the agreement between CRP and ESR values have included selected samples of patients with specific inflammatory diseases. 10,[13][14][15][16][17][18][19][20] More general studies comparing ESR and CRP have included patients with various diseases in the hospital [21][22][23][24][25][26] and primary care settings. [27][28][29] In general, CRP and ESR have similar diagnostic accuracy assessing acute inflammation, 10 though CRP tends to be more reliable for disease monitoring because CRP levels change faster than the ESR 12,26,27 and are less affected by patient age.…”
Section: Introductionmentioning
confidence: 99%
“…Values were obtained with a 1:8 dilution of supernatants. For an explanation of groups I through IV, see useful for monitoring disease activity in certain patient groups (4,6). This is probably because CRP production is stimulated by IL-1 (9).…”
mentioning
confidence: 99%
“…Therefore, CRP is considered superior to ESR on clinical, scientific and practical grounds [32,33] . Our findings on patients with lower respiratory tract infections corroborated this point of view, as we found higher and more discriminant responses of CRP than ESR.…”
Section: Discussionmentioning
confidence: 99%
“…We found that ESR was the second more useful parameter, only after CRP, for the differentiation between pneumonia and OALRTI, according to ROC curves, but its accuracy was lower than that CRP and in fact, it was excluded from the multivariate model owing to the higher weight of CRP. In addition to this better performance, the higher sensitivity and quicker and broader changes of CRP as compared with ESR [32,33,45] and the quickness of its determination [46,47] makes CRP the acute-phase reactant of choice for acute lower respiratory tract infections.…”
Section: Discussionmentioning
confidence: 99%